2017
DOI: 10.1016/j.clnu.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol intake and cardiovascular risk factors in a population with type 2 diabetes: The TOSCA.IT study

Abstract: http://www.clinicaltrials.gov; Study ID number: NCT00700856.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 32 publications
3
41
1
Order By: Relevance
“…For instance, mean polyphenol intake of an adult subject is about 283–1000 mg of total polyphenols/day in France [10, 11], 500–1100 mg/day in Spain [12], about 700 mg/d in Italy [13, 14], 890 mg/day in Finland [15], 534 mg/day in Brazil [16], and around 1500 mg/day in Japan [17], while total flavonoid intake is about 190 mg/day in the UK and Ireland [18], about 240–350 mg/day in the US [19, 20], around 450 mg/day in Australia [21], between 50 and 500 mg/day in China [22], and around 320 mg/day in Korea [23]. In addition, there is a great variability in polyphenol intake within countries depending on the type of diet consumed.…”
Section: Phenolic Compounds: Occurrence Intake and Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mean polyphenol intake of an adult subject is about 283–1000 mg of total polyphenols/day in France [10, 11], 500–1100 mg/day in Spain [12], about 700 mg/d in Italy [13, 14], 890 mg/day in Finland [15], 534 mg/day in Brazil [16], and around 1500 mg/day in Japan [17], while total flavonoid intake is about 190 mg/day in the UK and Ireland [18], about 240–350 mg/day in the US [19, 20], around 450 mg/day in Australia [21], between 50 and 500 mg/day in China [22], and around 320 mg/day in Korea [23]. In addition, there is a great variability in polyphenol intake within countries depending on the type of diet consumed.…”
Section: Phenolic Compounds: Occurrence Intake and Bioavailabilitymentioning
confidence: 99%
“…In the TOSCA.IT study with type 2 diabetic patients, high polyphenol intake is associated with slightly lower levels of LDL and triglycerides and higher levels of HDL cholesterol [14]. In the Moli-sani cohort, higher intakes of polyphenols were associated with lower total and LDL cholesterol, lower triglycerides, and higher levels of HDL cholesterol [69].…”
Section: Effects Of Polyphenol Intake On the Metabolic Syndromementioning
confidence: 99%
“…Accumulating evidence suggests that many dietary factors like antioxidants (polyphenols) are used alone or in combination with traditional/conventional chemotherapy to prevent or treat cancer [26][27][28][29][30][31][32][33][34][35]. Crude and processed plant extracts are studied extensively to evaluate its role in treatment as chemopreventive drug or to use in combination that can synergistically improve the outcome of current chemotherapy and lower the toxicity [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Crude and processed plant extracts are studied extensively to evaluate its role in treatment as chemopreventive drug or to use in combination that can synergistically improve the outcome of current chemotherapy and lower the toxicity [36][37][38]. European Prospective Investigation into Cancer and Nutrition is one such agency that studies the relationship between diet and cancer [29,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies indicated that diet is one of the factors, which might prevent diabetes and its complications (94). The TOSCA-IT (the influence of dietary fat and carbohydrates proportions on plasma lipids, glucose control and low-grade inflammation in patients with type 2 diabetes) study demonstrated that a diet characterized by a higher intake of total polyphenols was associated with a better cardiovascular risk factors profile and a lower grade of subclinical inflammation in population with diabetes mellitus type 2 (95).…”
Section: Diabetes Mellitusmentioning
confidence: 99%